PENCIPTAAN BUKU PANDUAN WISATA RELIGI ISLAM DENGAN PENDEKATAN KEARIFAN LOKAL BUDAYA SEBAGAI DESTINASI PARIWISATA KOTA SURABAYA - Puspasari, Dwinata; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: Traces of Islamic civilization star of the 15th century until now left several markes that have historical value of the struggle of the guardian and religious leaders in preaching and spreading Islam. The existence of the mosque and the tomb is a marker that holds many memories and deserves to be imitated. Along with the development of todayâs modern era the high demands of life and activity, the emergence of various facilities and infrastructure make the marker shifted and less aware of its existence. This book serves as a guide in addition to introducing the history of the struggle of the trustees and religious leaders in preaching and spreading Islam also simultaneously provide direction to find Islamic religious tourist destination in Surabaya including: Ampel Mosque, Jami Peneleh, Yellow Flower Rachmad Masjid, Masjid Chenghoo, Great Mosque of Al-Akbar. Hopefully with this manual can provide the knowledge and the ease of Islamic religious tourism in Surabaya.Â Keywords: Religiousitas, Islam, Handbook, Destinations, Tourism.Â